In Vitro Antibacterial Activity of Ethanolic Extract Derived from Leaves of Sansevieria aethiopica Thunb. (Asparagaceae) - Maryniuk, Myroslava; Tkachenko, Halyna; Buyun, Lyudmyla; Kurhaluk, Natalia; Góralczyk, Anna; Tomin, Władimir; Osadowski, Zbigniew (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2020)
This study was performed to assess the antibacterial properties of ethanolic extract prepared from Sansevieria aethiopica leaves against Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa strains, сlinically important bacteria, which are indicator organisms commonly used in various projects in order to monitor antibiotic resistance. For this study, а panel of organisms including Staphylococcus aureus ATCC 25923 (mecA negative), S. aureus ATCC 29213 (mecA negative, Oxacillin sensitive, weak β-lactamase-producing strain), S. aureus NCTC 12493 (mecA positive, Methicillin-resistant, EUCAST QC strain for cefoxitin), Escherichia coli ATCC 25922, E. coli ATCC 35218, Pseudomonas aeruginosa ATCC 27583 were used. The results of antibacterial assays showed that plant extract has exhibited the highest antibacterial activity against S. aureus as compared to the E. coli and P. aeruginosa strains. The diameters of inhibition zones were (26.35 ±1.26) mm, (16.15 ±1.47) mm, and (21.6 ±1.23) mm for S. aureus ATCC 25923, S. aureus ATCC 29213, and S. aureus NCTC 12493, respectively. Conversely, the extract has shown less antimicrobial activities against P. aeruginosa. The mean of the inhibition zone was (12.49 ±1.09) mm. Finally, the ethanolic extract of S. aethiopica leaves exhibited mild antibacterial activity against E. coli [mean of inhibition zone ranged (18.62 ±1.32) mm for E. coli ATCC 25922 and (16.38 ±1.02) mm for E. coli ATCC 35218]. Thus, the extract obtained by leaves of Sansevieria aethiopica showed potent antimicrobial activity. It can be assumed that the presence of the plant extracts could be used for the treatment of various infections because of its effective zone of inhibition of bacteria growth. However, isolation and characterization of the active ingredients in this plant together with their mechanisms of actions on pathogens are still open for further investigations.